The impacts of universalization: A case study on Thailand's social protection and universal health coverage - Prapaporn Tivayanond; Piya Hanvoravongchai (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper examines the impact of universal health security in Thailand and probes the impacts of the 30 Baht health policy objectives, poverty and inequality. The paper begins with an understanding of health policy as couched in the broader perspective of social protection. An understanding of social protection systems and health policy frameworks requires an awareness of institutional development specific to the national context. Here, research on government processes in allocating funds and their planning contributes to an expansive understanding of the comprehensive outcomes linked to the health policy frameworks. In order to analyse the policy process and identify key drivers for the universalization of health care in the country, the paper focuses on both direct and indirect impacts on the programme objectives as well as the structure of policy making. By assessing the direct and indirect impacts of the 30 Baht health policy, the paper draws out the trend of social security extension and examines the policy and institutional linkages between health care and other policies of the country. The paper is divided into five parts. The first part provides an overview of the conceptual thinking of "comprehensive outcomes" and social protection categories. The second part of the research focuses on social protection and health-care access in Thailand. Health financing reform and the path toward universal health coverage (UHC) in the country are addressed in depth in part three. The fourth part describes the comprehensive outcomes of the UHC movement by delineating between the direct and indirect impacts. And finally, the fifth part advances the discussion and conclusion of the research.
Keywords: 330